Bank profitability analysis and forecasting: Lithuania case - Viktorija Skvarciany; Justina Simanavičiūtė (Trends Economics and Management, 2018)
Purpose of the article: The purpose of this paper is to analyse commercial banks operating in Lithuania in terms of profitability, as it is one of the critical factors of economic development. Moreover, the profitability of commercial banks is a crucial factor for banks' financial stability which, in turn, has an impact on the stability of the whole financial system of a country. Variables representing banks profitability are as follows: return on equity (ROE), return on assets (ROA), and return on risk assets (RORA). What is more, the forecast of the abovementioned variables was made in order to predict their values. Methodology/methods: In order to analyse and assess the dynamics of the profitability indicators (ROA, ROE, RORA), the financial reports of six banks operating in Lithuania were analysed. After analysing the profitability indicators, the forecasts for three years were made using a moving average method. Scientific aim: To analyse commercial banks profitability indicators and make a forecast. The forecast of the indicators makes it possible to conclude that the banking system of Lithuania will continue to carry out profitable activities. Findings: The findings of the research showed that the estimated values of ROA, ROE and RORA are stable. The results of indicators forecasting makes showed that the banking system of Lithuania would continue to carry out profitable activities. Conclusions: Summarising the indicators of profitability group: return on equity, return on assets, and assets and equity ratio, it can be argued that the Lithuanian banking system is able to manage resources efficiently, in order to ensure the profitability of operations, despite market disturbances, such as the financial crisis of 2008.
Keywords: G21; M21; 650; commercial bank; return on assets; return on equity; return on risk assets; moving average